Highly Automated Electron Energy-Loss Spectroscopy Elemental Quantification. (10th April 2014) - Narayan, Raman D.; Weiss, J. K.; Rez, Peter
Abstract A model-based fitting algorithm for electron energy-loss spectroscopy spectra is introduced, along with an intuitive user-interface. As with Verbeeck & Van Aert, the measured spectrum, rather than the single scattering distribution, is fit over a wide range. An approximation is developed that allows for accurate modeling while maintaining linearity in the parameters that represent elemental composition. Also, a method is given for generating a model for the low-loss background that incorporates plural scattering. Operation of the user-interface is described to demonstrate the ease of use that allows even nonexpert users to quickly obtain elemental analysis results.